Associations of Infant Feeding and Timing of Weight Gain and Linear Growth during Early Life with Childhood Blood Pressure: Findings from a Prospective Population Based Cohort Study. - Marieke de Beer; Tanja G M Vrijkotte; Caroline H D Fall; Manon van Eijsden; Clive Osmond; Reinoud J B J Gemke (PLoS ONE, 2016)
Small birth size and rapid postnatal growth have been associated with higher future blood pressure. The timing of these effects, the relative importance of weight gain and linear growth and the role of infant feeding need to be clarified.We assessed how blood pressure relates to birth weight, infant and childhood growth and infant feeding (duration of exclusive breastfeeding and timing of introduction of complementary feeding) in 2227 children aged 5 years from a prospective cohort study (Amsterdam Born Children and their Development). Postnatal growth was represented by statistically independent measures of relative weight gain (weight gain independent of height) and linear growth in four age periods during infancy (0-1 month; 1-3 months; 3-6 months; 6-12 months) and from 12 months to 5 years.Lower birth weight was associated with higher childhood diastolic blood pressure (-0.38 mm Hg.SD-1; P = 0.007). Faster relative weight gain and linear growth after 1 month were positively associated with systolic and diastolic blood pressure. Associations of linear growth with systolic blood pressure ranged from 0.47 to 1.49 mm Hg.SD-1; P<0.01 for all. Coefficients were similar for different periods of infancy and also for relative weight gain and linear growth. Compared to breastfeeding <1 month, breastfeeding >1 month was associated with lower blood pressure (e.g. >6 months -1.56 mm Hg systolic blood pressure; P<0.001). Compared to >6 months, introduction of complementary feeding <6 months was associated with higher blood pressure (e.g. 4-6 months 0.91 mm Hg systolic blood pressure; P = 0.004).After the age of one month faster growth in either weight or height is associated with higher childhood blood pressure. It is unknown whether faster weight gain and linear growth carry the same risk for adult hypertension and cardiovascular morbidity. Longer breastfeeding and delayed introduction of complementary feeding may be associated with lower adult blood pressure.